Analysis of Physicochemical Properties of Bidara Leaves (Ziziphus spina-christi L.) Dried using Tray Dryer at Different Temperatures - Al Fira Safitri; Devi Tanggasari (Department of Pharmacy, Bumigora University, 2023)
The Bidara plant (Ziziphus spina-christi L) is a kind of small evergreen tree. Bidara plants are easy to find in Indonesia, especially in Sumbawa Regency, West Nusa Tenggara. Bidara leaves have many pharmacological potentials, including antioxidants, antibacterial, antiparasitic and anti-cancer. Bidara leaves can be developed into efficacious herbal products. The drying process greatly affects the quality of bidara leaves. Temperature in the drying process is an important factor because it can affect the content of bioactive compounds in bidara leaves. The purpose of this study was to determine the effect of drying temperature on physical and chemical properties. The dryer used in this drying is a tray dryer. The experimental design used in this study was a completely randomized design (CRD) with one factor. The temperatures used were 45, 50 and 55°C with a drying time of 3 hours. The results showed that the drying temperature affected the physical and chemical properties of bidara leaves. The best treatment for drying bidara leaves is drying at 55°C for a weight loss of 90.8%; water content 33.8% and temperature 45℃ for protein content 14.23%; Flavonoid content 11.71%.